Міжнародно-правове регулювання праці в рибальському секторі - Вихренко, Катерина Петрівна; Vikhrenko, Kateryna P.; Вихренко, Екатерина Петровна (Одеса, 2015)
Дисертацію присвячено міжнародно-правовим засадам регулювання праці у рибальському секторі. Висвітлено еволюцію моделей праці у рибальському секторі та його місце у системі міжнародного правового регулювання. Досліджено розвиток правового регулювання праці у рибальському секторі під егідою МОП та його кодифікацію, визначено специфіку правового регулювання праці у рибальському секторі в актах ММО та ФАО. Окреслено процеси відображення міжнародних правових стандартів праці у рибальському секторі у праві ЄС. Узагальнено специфіку імплементації цих міжнародних стандартів у право іноземних держав та визначено особливості практики їх застосування в Україні. Міжнародно-правове регулювання праці у рибальському секторі визначено як процес утворення, реалізації, імплементації та виконання норм міжнародних договорів, схвалених під егідою ООН, ММО, МОП та ФАО, щодо трудових та пов’язаних з ними відносин членів екіпажів (персоналу, рибалок) на риболовних суднах, що здійснюють власну діяльність в рамках їх мореплавства. Реалізація, імплементація та виконання цих норм відбувається шляхом схвалення актів права ЄС, національного законодавства, положень галузевих та колективних угод, утворення організаційних механізмів підготовки, контролю, охорони праці, ведення тристороннього діалогу, розслідування інцидентів у рибальському секторі.

Диссертация посвящена международным правовым основам регулирования труда в рыболовном секторе. Рассматривается эволюция моделей работы в рыболовном секторе и его место в системе международного правового регулирования. Исследовано развитие правового регулирования труда в рыболовном секторе под эгидой МОТ и его кодификация. Определяется специфика правового регулирования труда в рыболовном секторе в актах ММО и ФАО. Очерчены процессы отображения международных правовых стандартов труда в рыболовном секторе в праве ЕС. Определены специфика имплементации этих международных стандартов в праве иностранных государств, особенности практики их применения. Международно-правовое регулирование труда в рыболовном секторе определено как процесс реализации, внедрения и выполнения норм международных договоров, одобренных под эгидой ООН, ММО, МОТ и ФАО, в трудовых и связанных с ними отношениях членов экипажей (персонала, рыбаков) на рыболовных судах, осуществляющих свою деятельность в рамках мореплавания. Реализация, имплементация и выполнение этих норм происходит путем принятия актов права ЕС, национального законодательства, положений отраслевых и коллективных соглашений и договоров, организационных механизмов подготовки, контроля, охраны труда, ведения трехстороннего диалога, расследования инцидентов в рыболовном секторе.

The thesis is dedicated to the international legal grounds of regulation the labour relations in the fishing sector. The evolution of labour models in this sector and its place in the international legal regulation are lighted at. The development of international legal regulation of labour in the fishing sector under the auspices of the ILO, also as its codification in XXI cent., are investigated, the specific features of international legal regulation of labour in this sector in acts of IMO and FAO are determined at. Processes of reflecting into EU law the international legal standards of labour in the fishing sector are outlined. Author made the overview of specifics the implementation of those labour international standards in the right of foreign countries and lighted the peculiarities of such implementation practices in Ukraine. International legal regulation of labour in the fishing sector is defined as the process of implementation, realization and enforcement of the international agreements` norms approved by aegis the UN, IMO, ILO and FAO on labour and related relations of the fishing vessels` crew members (staff, fishermen) carrying out their activities within shipping. Such implementation, realization and enforcement of those standards is being through the acts of approval of the EU law, the national laws, the regulations of sector and collective agreements, the institutional mechanisms` preparation, monitoring, providing labor safety, holding trilateral dialogue, investigating incidents in the fishing sector. Thesis shows the mechanisms of application to regulate the labour relations in fishing sector the norms of the UN Convention on the Law of the Sea, 1982; the UN Agreement for the Implementation of the Provisions of the UNCLOS, 1982 relating to the Conservation and Management of Straddling Fish Stocks and Highly Migratory Fish Stocks, 1995; the Agreement to Promote Compliance with International Conservation and Management Measures by Fishing Vessels on the High Seas, 1993; the Torremolinos International Convention for the Safety of Fishing Vessels, 1977, superseded by the Torremolinos Protocol, 1993 and by the Cape Town Agreement, 2012; the International Convention on Standards of Training, Certification and Watchkeeping for Fishing Vessel Personnel (STCW-F), 1995; the ILO Convention Concerning Work in the Fishing Sector № 188, 2007, other ILO conventions and recommendations etc. Author proves that national legislation and sector collective agreements, also as the legal practice for fishermen labor have significant differences in modern countries, particularly in the implementation of international standards. The main differences are in relation to fishermen as to the employees or as to the self-employed individuals, in the status of national fishermen associations, in priority of collective or sector agreements for establishing basic conditions of individual labour contracts fishermen and others. Anyway the developed countries implement now not only the demands of conventions that are in force, such as STCW-F, but also the norms of agreements that are not in force but have the significant importance for fishing sector, such as Torremolinos Convention, Protocol and Agreement or ILO Convention № 188.
дис. ... к.ю.н. : 12.00.11
Вихренко К. П. Міжнародно-правове регулювання праці в рибальському секторі : дис ... к.ю.н. : 12.00.11 / Вихренко Катерина Петрівна. - Одеса, 2015. - 237 арк.
Keywords: міжнародне трудове право; рибальський сектор; міжнародні договори; праця рибалок; рибальські (риболовні) судна; галузеві угоди; колективні договори; ММО; МОП; ФАО; международное трудовое право; рыболовный сектор; рыболовные судна; труд рыбаков; международные договоры; отраслевые соглашения; коллективные договоры; МОТ; international labor law; fishermen labor; fishing sector; fishing vessels; international agreements; collective agreements; sector agreements; ILO; IMO; FAO